Molecular structures of thymidine isomers isolated in low-temperature inert matrices: Biological Systems at Low Temperatures - Ivanov, A.Yu.; Krasnokutski, S.A.; Sheina, G.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The Fourier transform infrared spectra of 2`-deoxyribonucleoside — thymidine (dT) in low-temperature Ar matrices are obtained in the range 4000–1300 cm–1. It is determined that anti-conformers of thymidine are dominant. The ribose rings of the main anti-conformers dT_a0, dT_a1 are in the C2`-endo conformation, but the ribose rings of minor anti-conformers dT_a2, dT_a3 have the C3`-endo conformation, stabilized by intramolecular hydrogen bonds O3`H…O5` and O5`H…O3`, respectively. The main syn-conformer dT_s2 is stabilized by the intramolecular hydrogen bond O5`H…O2 and has C2`-endo conformation of the ribose ring.